New Model for the Yeast RNA Polymerase I Transcription Cycle - Aprikian, Pavel (American Society for Microbiology, 2001)
Using an immobilized template assay, we observed two steps in assembly of the yeast RNA polymerase I (Pol I) preinitiation complex: stable binding of upstream activating factor (UAF) followed by recruitment of Pol I-Rrn3p and core factor (CF). Pol I is required for stable association of CF with the promoter and can be recruited in the absence of Rrn3p. Upon transcription initiation, Pol I-Rrn3p and CF dissociate from the promoter while UAF remains behind. These findings support a novel model in which the Pol I basal machinery cycles on and off the promoter with each round of transcription. This model accounts for previous observations that rRNA synthesis may be controlled by regulating both promoter accessibility and polymerase activity.